GEREJAYANG BERTUMBUH TANPA BAALISME - Magdalena Tanusaputra; Yanto Paulus Hermanto; Ferry Simanjuntak (Sekolah Tinggi Teologia Wesley Methodist Indonesia, 2021)
ABSTRACT One characteristic of church growth is the increasing number of churches. Churches take a variety of ways to increase the number of their congregations. Some are in a biblical way and some are not. Methods or methods which are not biblical are known as means of baalism. And the church often uses these methods. Therefore, the authors conduct research related to this so that churches use biblical methods in their implementation. The research method used is a descriptive qualitative approach and an approach that is taken from examples in the Bible relating to church development. From the results of this research, it is hoped that churches will make efforts to increase the number of their congregations in biblical ways and not using Baalism.